The impact of the use of a program to guide the adjustment of the trends of female students towards students with educational difficulties in the city of Riyadh- Experimental Study - Al-Ayadhi, Mayssa Abdullah (Journal of Educational and Psychological Sciences, 2019)
The aim of this study was to establish an orientation program to change the trend of the regular students towards their learning difficulties, to increase their level of knowledge and to increase their acceptance and interaction with them. The study sample consisted of 15 students from grades 4, 5 and 6, Riyadh, which has a resource room. The following tools have been implemented: A questionnaire on the trend of the regular students towards people with learning difficulties, and pilot programs have been applied to the experimental group members in order to make the change required by the regular students towards their difficult peers Scientific studies enrolled in the resource roomThe results of the study are based on the results of the averages for the benefit of the experimental group, which means that the students of the experimental group have improved their positive attitudes toward their learning disabilities. This may be due to the comfortable atmosphere in the program they participated in. The techniques, strategies and practices included in the guidance program used in the study as a simulation method that raises the level of acceptance of learning disabilities and the role that the normal student can play with them has had a clear reflection on the impact on the trend of female studentsIt is possible to predict the retention of students from the experimental group in the direction acquired in the program and stay in their minds as long as possible and often raises the level of awareness and knowledge and understands the nature of the person who This is reflected in his feelings and begins to show his understanding, compassion and flexibility when dealing with him
Keywords: counseling program; orientation towards people with learning disabilities; learning disabilities